2015
DOI: 10.11648/j.ajep.20150404.15
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Stock Variations Along Altitudinal and Slope Gradient in the Forest Belt of Simen Mountains National Park, Ethiopia

Abstract: Abstract:Forests play a significant role in climate change mitigation by sequestering and storing more carbon from the atmosphere which is released by anthropogenic causes. The overall objective of this study was to measure Variations of Carbon Stock along Altitudinal and Slope Gradient in the forest belt of Simen Mountains National Park. And it aimed to add values of the lowland forest belt of the park for climate change mitigation contribution in Ethiopia. The work was accomplished properly using random samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
1
0
2
Order By: Relevance
“…On the other hand, it has been reported by many studies as live biomass carbon increase with altitude increases [25,32,33]. In the present study, the middle altitude takes the most AGB and BGB carbon storage and much more depleted carbon storage observed on higher altitude, this result consistent with [34]. Based on the mean result, relatively it is possible to say as altitude decreases biomass carbon increases.…”
Section: Carbon Stocks Variation Along Altitudinal Gradientsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, it has been reported by many studies as live biomass carbon increase with altitude increases [25,32,33]. In the present study, the middle altitude takes the most AGB and BGB carbon storage and much more depleted carbon storage observed on higher altitude, this result consistent with [34]. Based on the mean result, relatively it is possible to say as altitude decreases biomass carbon increases.…”
Section: Carbon Stocks Variation Along Altitudinal Gradientsupporting
confidence: 89%
“…Though [34] study found that deadwood biomass carbon in all altitude classes with more carbon stock in middle altitude, the present study, reported that deadwood biomass carbon found only in lower altitude. Deadwood biomass carbon found only in lower altitude.…”
Section: Carbon Stocks Variation Along Altitudinal Gradientcontrasting
confidence: 72%
“…The soil carbon in highland and lowland was lower than midland (Table 6), this might be due to rugged topographic nature of the highland that facilitate runoff and the higher temperature of the lowland that facilitate oxidation, which is in line with Demessie, Singh, and Lal (2016). The total carbon stock of landuses surrounding rural wooden houses that include grass covered wooden house decreased as the altitude decreased from highland (49.26 kg C m -2 ) to lowland (28.35 kg C m -2 ), and remnant woody plants from highland (29.4 kg C m -2 ) to lowland (2.68 kg C m -2 ) of the present study area as studied in Mwakisunga and Majule (2012) but opposes the total carbon stock studied by Simegn and Soromessa, (2015). The decrease in carbon storage with increased depth of soil (Table 6) was comparable with other studies carried out elsewhere (Tesfaye et al, 2016).…”
Section: Soot Organic Carbon Accumulation Of Wooden Housescontrasting
confidence: 44%